PRODUKTIVITAS PRIMER FITOPLANKTON DAN KEANEKARAGAMAN JENIS FAUNA MAKROBENTHOS BERDASARKAN KERAPATAN MANGROVE - Amrullah Taqwa; Supriharyono Supriharyono; Ruswahyuni Ruswahyuni (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2010)
The studies of phytoplankton primary productivity and diversity of macrobenthic fauna in different density of mangrove were carried out from May to June 2009 in mangrove conservation area, in Tarakan, East-Kalimantan, Indonesia. Content of chlorophyll-a converted to phytoplankton primary productivity by Strickland formula. Diversity of macrozoobenthos calculated with Shannon’s Index. Phytoplankton primary productivity in high, middle and low density of mangrove are 50.13±5.53 mgC/m3/d; 45.32±6.48 mgC/m3/d and 41.48±6.48 mgC/m3/d respectively. Shannon’s index value in low, middle and high density of mangrove are 2.24-2.61; 1.33-2.51 and 1.35-2.51 respectively. The results of this study showed a strong correlation betweeen diversity of macrobenthic fauna and the density of mangrove (Contingency coefficient = 0.554; Sig.= 0.147)Key words: mangrove, phytoplankton, diversity, macrobenthos.